Factores de riesgo asociados al embarazo en adolescentes atendidas en el Hospital General Guasmo Sur, Guayaquil, septiembre 2024 - abril 2025. - Alvarado Goyes, Kristel Pierina (2025)
Adolescent pregnancy is a public health problem with serious social, economic and medical implications. This study analyses the risk factors associated with adolescent pregnancy in patients seen at the Hospital General Guasmo Sur, in Guayaquil, during the period September 2024 - April 2025. The main objective was to determine the socioeconomic, family and cultural risk factors that influence the incidence of adolescent pregnancy. The methodology used was quantitative, descriptive and field-based, with a non-experimental and cross-sectional approach. Structured surveys were administered to a sample of 259 randomly selected pregnant adolescents, and an analysis of clinical records was carried out. The results showed that the majority of pregnant adolescents are between 15 and 17 years old, come from low-income families and lack access to comprehensive sexuality education and contraceptive methods. In addition, 65 per cent of respondents reported that sexual and reproductive health is not discussed in their homes, and 40 per cent have not completed secondary education, suggesting a link between pregnancy and school dropout. Socio-economic, educational and family actors have a significant influence on the incidence of adolescent pregnancy. It is recommended to strengthen sex education in educational institutions, improve access to contraceptives and promote family dialogue on sexual health to prevent unplanned pregnancies in adolescents.